2020
DOI: 10.1007/s00062-020-00879-1
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Localization of the Primary Sensorimotor Cortex in Gliomas

Abstract: Purpose Functional magnetic resonance imaging (fMRI) has an established role in neurosurgical planning; however, ambiguity surrounds the comparative value of resting and task-based fMRI relative to anatomical localization of the sensorimotor cortex. This study was carried out to determine: 1) how often fMRI adds to prediction of motor risks beyond expert neuroradiological review, 2) success rates of presurgical resting and task-based sensorimotor mapping, and 3) the impact of accelerated resting fMRI acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Studies have shown that anatomical reviews of high-resolution T1-weighted three-dimensional sequence images by expert neuroradiologists are highly effective in locating the ipsilesional central sulcus and thus sensory and motor cortex with accuracy up to 98.6%. 6 Motor task-based fMRI also succeeded in 100%, while conventional rs-fMRI failed to localize a sensorimotor network in up to 14.1% of patients. The temporal accelerated rs-fMRI is reported with results same as that of task-based fMRI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have shown that anatomical reviews of high-resolution T1-weighted three-dimensional sequence images by expert neuroradiologists are highly effective in locating the ipsilesional central sulcus and thus sensory and motor cortex with accuracy up to 98.6%. 6 Motor task-based fMRI also succeeded in 100%, while conventional rs-fMRI failed to localize a sensorimotor network in up to 14.1% of patients. The temporal accelerated rs-fMRI is reported with results same as that of task-based fMRI.…”
Section: Discussionmentioning
confidence: 98%
“…The sensorimotor network includes somatosensory and motor regions and extends to the SMAs. 5 The sensorimotor network shows tight anatomico-functional coupling; 6 this network is activated during motor tasks such as finger tapping indicating that these regions may involve a premediated state that ready the brain when performing and coordinating a motor task. 5 rs-fMRI was performed because of inability to do required tasks, which showed BOLD signal along sensorimotor network and it was limited by the tumor on the right side as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our findings indicate that the presence of a highly malignant tumor in the SM cortex determines relevant changes with respect to the normal activation conditions and in a way that requires evaluating which is the affected hand and whether it is the dominant one. Unfortunately, this evaluation does not typically occur in the clinical practice (see [ 11 , 12 , 13 ]). We observe significant changes to take place in the hemisphere harboring the lesion but, to a certain extent, in the healthy hemisphere, too.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning data analyses, we cannot exclude SM cortex activation to be influenced by mass effect and potential neurovascular uncoupling [ 35 , 36 ], even though several studies reported reliability of functional SM activations even in the presence of high-grade lesions [ 13 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation